Implementation of Work Motivation on the Quality of Public Services at The Bangkala Village Office, Maiwa District, Enrekang Regency - A. Marsal Husain; Kamaruddin Sellang; Andi Astinah Adnan (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study focuses on the "Implementation of Work Motivation on the Quality of Public Services at the Bangkala Village Office, Maiwa District, Enrekang Regency." The research investigates the implementation of work motivation efforts to enhance employee enthusiasm, dedication, and productivity within a workplace setting. It explores various strategies employed by leaders to encourage employees to work more effectively and achieve organizational goals. A quantitative descriptive method was employed, involving a sample of 97 respondents who received services from February to April 2024, selected through non-probability sampling. Data collection methods included observation, interviews, literature reviews, and questionnaires. Data analysis was performed using descriptive statistical analysis, validity tests, reliability tests, and simple linear regression analysis with SPSS version 21.The findings reveal that the implementation of work motivation significantly affects the quality of public services at the Bangkala Village Office, with 83.4% of the service quality being influenced by work motivation. The study also identifies key factors such as responsibility in task performance, self-development, and work environment conditions that substantially impact the effectiveness of work motivation implementation. The hypothesis test results support the conclusion that work motivation implementation positively influences public service quality.